An Analysis of the Introduction to Thai Language Textbooks for Foreigners - Sakchaisomboon, Sumonta (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This study aims to analyze and compare Thai language lessons for foreigners in terms of learning methods and contents, focusing on 1) Thai language textbook for foreigners produced and published by Office of Higher Education Commission or other Ministries and used nationwide, 2) Thai language textbook for foreigners produced and published by Thai universities or other education institutes with the expertise in teaching Thai language for foreigners, and 3) commercial textbook produced and published by private sectors. The findings revealed that there are both similarities and differences among the three textbooks on Thai language lessons for foreigners in terms of learning methods and contents. Most textbooks use phonetic alphabets for learners’ correct pronunciation. However, the learning methods and objectives of each textbook are different according to the target learners and their learning methods; self-study and in-class learning. Audio CDs are also used as part of the teaching materials except when the learning situation is held in the context of Thai society where learners are directly exposed to the language.